ANALISIS PENGARUH KEY PERFORMANCE INDICATOR, PENETAPAN TARGET PAJAK, DAN JOB GRADE SYSTEM TERHADAP KINERJA KARYAWAN KPP PRATAMA KEBUMEN - Wiwoho, Gunarso (Fokus Bisnis : Media Pengkajian Manajemen dan Akuntansi, 2008)
The management performance is a process of ongoing communication which involves building hope and clear understanding of work functions that expect to be done by employees and how they give contribution to organizational goals. Employee performance in any organization is always running fluctuatively. It needs requiring the performance growth including in The tax Servicing Office (LTO) Pratama that influenced by the application of ‘key performance indicators, attention toward the tax decision and job grade system (system peningkatan pekerjaan) which has long been applied in the KPP Pratama Kebumen. The existence of this is the writer background to do the research titled ‘The Effect Analysis of ‘Key Performance Indicators, Tax Target Decision and Job Grade System toward The Employee Performance at The Tax Servicing office (Kantor Pelayanan Pajak (KPP)) Pratama Kebumen’ The respondents were 30 employees who work at KPP Pratama Kebumen. The research uses descriptive method and quantitative analysis by SPSS 16:00. By quantitative methods, It tested by validity, reliability, the assumptions of classical testing, the analysis of multiple regression, hypothesis testing by using the test ‘t’ or test ‘f’. The hypothesis testing of the test ‘t’ shows that all variables have a significant effect on the performance except for the variable application of key performance indicators. Whereas the test ‘f’ results that the application of key performance indicator, tax target decision and job grade systems that have a significant effect to the employee performance of KPP Pratama Kebumen. Key words: the application of key performance indicators, tax target decision, job grade system, employee performance, multiple regression.